Litho-paleoecological characteristics of the Upper Ordovician reef Bol'shaya Kos'yu (Ilych River, Northern Urals) - L. A. Shmeleva (Литосфера, 2016)
The litho-paleoecological characteristics of the Upper Ordovician reef Bol’shaya Kos’yu was given. The reef paleolandscape profile - reef plateau, reef internal lagoons, and frontal reef zone was determined, and reef facies were described. The distribution of fossils involved in the reef Bol’shaya Kos’yu formation was shown. The evolution of reef ecosystem was traced. The ecological succession fore stages were identified: stabilization, colonization, diversification and domination which reflex the complex ecosystem structure of this reef.